Towards the alignment of conceptual mastery and teaching practice competence: A case study in vocational education - Hafid Rahmandan; Retno Eka Pramitasari; Nahindi Putra Gitama (Eduvista: Journal of Education and Innovation, 2026)
The alignment between conceptual mastery and teaching practice competence has rarely been examined in small classes through individual pattern analysis, leaving their relationship insufficiently understood. This study aimed to identify the alignment pattern between students' conceptual mastery and teaching practice competence in vocational education. A case study approach with qualitative analysis following the Miles, Huberman, and Saldaña model was employed using participation, assignment, midterm examination, and micro teaching assessment data. The findings revealed that all students with complete data demonstrated a positive alignment pattern, with teaching practice scores consistently exceeding conceptual mastery scores by 7–10 points. These results indicate that conceptual understanding develops into teaching competence through learning that integrates theory with authentic teaching practice. This study also proposes a conceptual model explaining the relationship among conceptual mastery, teaching practice competence, pedagogical implications, assessment improvement, and educational quality in vocational education. Abstrak Keselarasan antara penguasaan konsep dan kompetensi praktik mengajar masih jarang dikaji pada kelas berukuran kecil melalui analisis pola individu, sehingga hubungan keduanya belum dipahami secara komprehensif. Penelitian ini bertujuan mengidentifikasi pola keselarasan antara penguasaan konsep dan kompetensi praktik mengajar mahasiswa dalam pembelajaran kejuruan. Penelitian menggunakan pendekatan studi kasus dengan analisis kualitatif model Miles, Huberman, dan Saldaña terhadap data partisipasi, tugas, UTS, dan micro teaching (UAS). Hasil penelitian menunjukkan bahwa seluruh mahasiswa dengan data lengkap memiliki pola keselarasan positif, ditandai oleh capaian praktik yang secara konsisten lebih tinggi daripada capaian konseptual dengan selisih 7–10 poin. Temuan ini menunjukkan bahwa penguasaan konsep berkembang menjadi kompetensi praktik melalui pembelajaran yang mengintegrasikan teori dan pengalaman mengajar. Penelitian ini juga menghasilkan model konseptual yang menjelaskan hubungan antara penguasaan konsep, kompetensi praktik, implikasi pedagogis, pengembangan asesmen, dan peningkatan kualitas pendidikan kejuruan.